2007
DOI: 10.1111/j.1600-0625.2006.00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Tight junction proteins in keratinocytes: localization and contribution to barrier function

Abstract: Recent research suggests that tight junctions (TJs) are located in the stratum granulosum, where they contribute to the barrier function of the epidermis. In this study, we investigated the formation of functional TJs in cultured normal human epidermal keratinocytes. We observed the development of permeability barrier function through the process of Ca reversibly disrupted the continuous network of TJ proteins and the permeability barrier. We also found that the addition of ochratoxin A weakened the permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 31 publications
7
120
0
1
Order By: Relevance
“…Concerning the exact localization of the functional TJ barrier, it has been suggested that it is localized in human and murine skin in the mid layers of the SG 3,11,21 ; although other studies have found TJ barrier to be at the uppermost layer of the SG. 15 Using cultured keratinocytes, it was shown that, TJs form a barrier to water 24 and molecules of different size ( [24][25][26][27][28] ) as well as ions (e.g. Na C , Cl ¡ , Ca 2C ).…”
Section: Tj Composition and Function In Healthy Skin (And Cultured Kementioning
confidence: 99%
“…Concerning the exact localization of the functional TJ barrier, it has been suggested that it is localized in human and murine skin in the mid layers of the SG 3,11,21 ; although other studies have found TJ barrier to be at the uppermost layer of the SG. 15 Using cultured keratinocytes, it was shown that, TJs form a barrier to water 24 and molecules of different size ( [24][25][26][27][28] ) as well as ions (e.g. Na C , Cl ¡ , Ca 2C ).…”
Section: Tj Composition and Function In Healthy Skin (And Cultured Kementioning
confidence: 99%
“…Then transepithelial electric resistance (TER) was measured using a Millicell-ERS epithelial voltmeter (Millipore), as described in a previous study (6). TER by the keratinocyte sheet gives an indication of the transepithelial permeability of water-soluble ions.…”
Section: Transfection Of Keratinocytes With Myd88 Small Interfering Rnamentioning
confidence: 99%
“…In the murine epidermis, typical stratified epithelia, TJ structures are restricted to the stratum granulosum, where continuous TJs, including occludin, claudin-1, and claudin-4, were identified by immunofluorescence microscopy analyses (3,4). Furthermore, TJs function as paracellular barriers against small molecules in the human epidermis and cultured keratinocytes (5,6). However, the exact role of TJs in cutaneous barriers remains unclear in relation to that of the stratum corneum.…”
mentioning
confidence: 99%
“…Claudin-1 and claudin-4 in particular have been shown to be critical for the function of tight junctions [7].…”
Section: Introductionmentioning
confidence: 99%